FORMULASI SEDIAAN MASKER GEL PEEL-OFF KOPI ROBUSTA (Coffea canephora) DAN EFEKTIVITASNYA SEBAGAI ANTI PENUAAN DINI - Hanum, Tengku Ismanelly; Marianne, Marianne; Sumaiyah, Sumaiyah; Hasibuan, Poppy Anjelisa Zaitun; Hasibuan, Wan Fadilla; Bestari, Khansa Candra (Indonesian Journal of Pharmaceutical and Clinical Research, 2025)
Robusta coffee (Coffea canephora) contains several components that are good for facial skin, such as flavonoids which act as antioxidants. A peel-off gel mask is a skin care cosmetic preparation in the form of a gel and after being applied to the skin for a certain time until it dries, this preparation will form an elastic transparent film layer, so that it can be peeled off. This research aims to develop Robusta coffee into a peel-off gel mask preparation. off off which has appearance, pH, viscosity, spreadability, drying time, and its effectiveness as an anti-aging agent. The research stages carried out were the formulation of a 10% coprobusta peel-off gel mask, stability testing at room temperature for 12 weeks and the anti-aging effectiveness of the 10% corobusta peel-off gel mask. Stability test parameters include pH, viscosity, spreadability, and drying time. Test the effectiveness of anti-aging using a skin analysis tool with test parameters, namely air content, smoothness, pore size, number of blemishes and wrinkles. The results of this study show that the preparation is stable in all test parameters for 12 weeks of storage at room temperature, does not irritate the skin and has anti-aging activity on facial skin, namely increasing air content, smoother skin, smaller pores, reducing the number of blemishes and wrinkles over time. four weeks of treatment.